Treatment with glatiramer acetate in APPswe/PS1dE9 mice at an early stage of Alzheimer’s disease prior to amyloid-beta deposition delays the disease’s pathological development and ameliorates cognitive decline - Huang, Zengyong; Gong, Zhuo; Lin, Yongtai; Yang, Fan; Chen, Weiping; Xiang, Shaotong; Huang, Yuedong; Xiao, Hao; Xu, Shuwen; Duan, Jinhai (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is characterised by neuroinflammation, which is frequently accompanied by immune system dysfunction. Although the mechanism of neurodegenerative lesions is unclear, various clinical trials have highlighted that early intervention in AD is crucial to the success of treatment. In order to explore the potential of immunotherapy in the early period of AD, the present study evaluated whether application of glatiramer acetate (GA), an immunomodulatory agent approved for remitting-relapsing multiple sclerosis (RRMS), in the early stages of AD prior to amyloid beta (Aβ) deposition altered the Aβ pathology and cognitive impairments in APPswe/PSEN1dE9 (APP/PS1) transgenic mice. Methods: We treated two cohorts of pre-depositing and amyloid-depositing (2-and 6month-old) APP/PS1 mice with weekly-GA subcutaneous injection over a 12-week period. We then tested spatial learning and memory using the Morris water maze (MWM) and the Y maze. Immunohistochemistry staining was utilised to analyse Aβ burden in the brain as well as activated microglia. Furthermore, the inflammatory cytokine milieu within brains was estimated by quantitative real-time polymerase chain reaction, and the peripheral CD4 + CD25 + Foxp3 + regulatory T cells (Tregs) in the spleen were measured by flow cytometry. Results: We found that early GA administration reduced Aβ burden and ameliorated cognitive decline. Meanwhile, the immune microenvironment had changed in the brain, with an increase in the production of anti-inflammatory cytokines and a decrease in microglial activation. Interestingly, early GA administration also modulated the peripheral immune system through the amplification of Tregs in the spleen. Conclusion: Overall, our findings revealed that GA treatment might enhance the central and peripheral immune systems' protective capabilities in the early stages of AD, eventually improving cognitive deficits. Our research supports the advantages of immunomodulatory treatments for AD at an early stage..